William Gregory from The Innocents - T. Simon (Law Text Culture, 2006)
Artist: Taryn Simon Artwork: William Gregory Wick’s Parlor, Louisville, Kentucky With fiancée Vicki Kidwell, whom he dated prior to conviction Gregory was a pool champion in prison Served 7 years of a 70-year sentence